Answer:
[tex] \boxed{a = \frac{w}{ 6} - \frac{b}{2} + \frac{2}{3} } [/tex]
Step-by-step explanation:
[tex]Solve \: for \: a: \\
= > w=3(2a+b)-4 \\ \\
w=3(2a+b)4 \: is \: equivalent \: to \: 3(2a+b)-4= w: \\
= > 3(2a+b) - 4=w \\ \\
Expand \: out \: terms \: of \: the \: left \: hand \: side: \\ = > (3 \times 2a) + (3 \times b) - 4 = w \\
= > 6a+3b - 4=w \\ \\
Subtract \: 3b - 4 \: from \: both \: sides: \\ = > 6a + 3b - 4 - (3b - 4)=w - (3b - 4) \\ = > 6a = w - 3b + 4 \\ \\ Divide \: both \: sides \: by \: 6: \\ = > \frac{ \cancel{6}a}{ \cancel{6}} = \frac{w - 3b + 4}{6} \\ = > a = \frac{w}{6} - \frac{3b}{6} + \frac{4}{6} \\ = > a = \frac{w}{ 6} - \frac{b}{2} + \frac{2}{3} [/tex]